Nutritional guidelines including hydration recommendations and energy needs for the female athlete: Preventing low energy availability and functional amenorrhea through nutritional therapy - García-González, Á.; Robert-McComb, J. J. (The active female. Health issues throughout the lifespan, 2023)
The prevalence of secondary amenorrhea in athletes varies widely depending on sport, age, training volume, and body weight. Studies of different athletic populations report rates of menstrual disorders ranging from 1 to 69%. If examining only subclinical ovarian disturbances in athletes, the percentage increases to 70%; whereas, only about 2-15% of sedentary young women have menstrual irregularities. Studies have consistently shown that normal menstrual cycling is altered if there is a restriction in energy availability (EA). Energy availability is defined as energy obtained through oral nutrition minus energy expended during exercise. When EA falls below a certain threshold, the amount of energy used for cellular maintenance, thermoregulation, growth, and reproduction is compromised. This compensation promotes survival but impairs general overall health, specifically reproductive and bone health in females. Studies consistently show that female athletes do not consume enough energy to support their activity levels. Low EA and altered nutrient intake place these athletes at risk for nutrition-related disorders, such as amenorrhea, osteoporosis, iron-deficiency anemia, and eating disorders. Nutritional educational programs must be carefully designed by a multi-professional team and should involve not only the female athlete but also coaches and family to be successful in facilitating the adoption of healthy eating habits in athletes. A joint position statement by the American College of Sports Medicine, the American Dietetic Association, and the Dietitians of Canada states that a diet substantially different from that recommended in the Dietary Guidelines for Americans is not needed for athletes if enough calories are ingested to meet their energy needs. It is recommended that an athlete`s diet should consist of nutrient-dense food and beverages within and among the basic food groups while choosing foods that limit the intake of saturated and trans fats, cholesterol, added sugars, salt, and alcohol.